Stability constant of oxovanadium(IV)-levofloxacin complex in pure andbinary mixed solvents (Journal of Bangladesh Academy of Sciences, 2026)
The complexation between the oxovanadium(IV) ion and the levofloxacin (levH) was examined in pure solvents (water; H2O, dimethylformamide; DMF, and methanol; MeOH) and mixed solvents (dimethylformamidewater; DMF-H2O and methanol-water; MeOH-H2O) using the spectrophotometric method. The complexation reaction was also observed in aqueous solution (pH 2) at various ionic strengths and temperatures. The results indicate that the complex has a 1:2 stoichiometry in all pure and binary mixed solvents. The Harvey and Manning equation was used to calculate the stability constant (logβ) of the oxovanadium(IV)-levofloxacin [VIVO(lev)2] complex. In pure solvents, the logβ values of the [VIVO(lev)2] complex follow the order MeOH > H2O > DMF. The MeOH-H2O system has substantially larger logβ values than the DMF-H2O system. Changes in logβ versus the dielectric constant (1/D) of binary mixed solvents show a linear relationship. As ionic strength and temperature increase in aqueous solution, the stability constant of the [VIVO(lev)2] complex decreases. Based on the thermodynamic parameters (ΔG, ΔH, and ΔS), the complexation reaction between the oxovanadium(IV) cation and levofloxacin is spontaneous and exothermic.J. Bangladesh Acad. Sci 50(2); 207–214: June 2026